THE THOUGHTS OF ISLAMIC PHILOSOPHERS ISLAMIC EDUCATION PERSPECTIVE - Yazidul Busthomi (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2025)
To improve the quality of human resources, it must go through a good and directed educational process. Experts consider education to have an important role in efforts to instill a sense of religion in a child. Education is an activity to develop all aspects of human personality that lasts a lifetime. Education is intended to help students to develop their human potential. For the Indonesian people, education is interpreted as a national struggle. Al-Ghazali's thoughts on education in general are religious. This tendency is likely influenced by his mastery of Sufism. According to al-Ghazali, true education is a means to get closer to Allah SWT. Al-Qabisi in initiating his educational concept consists of children's education, educational goals and educational principles. Education according to Ibn Khaldun in general about the meaning of education is anyone who does not get an education from their parents, will be educated by the future.